Into a Deeper Understanding of Evolutionary Computing: Exploration, Exploitation, and Parameter Control Volume 1 - Abdul Halim, Abdul Hanif; Das, Swagatam; Ismail, Idris; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This book delves into fundamental and advanced strategies for enhancing evolutionary and metaheuristic algorithms, focusing on the vital balance between exploration and exploitation search mechanisms. As technological advancements increase optimization complexity, effectively managing this balance becomes crucial for achieving optimal solutions within reasonable computational resources. The book's distinctive structure organizes content according to optimization stages, offering a comprehensive discussion of various approaches supported by extensive literature.
Algorithm initialization categories and assessment -- Fundamental Tradeoffs between exploration and exploitation search mechanisms -- Distributions and Functions Driven.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence